PERBANDINGAN KINERJA KEUANGAN PEMERINTAH DAERAH SEBELUM DAN SETELAH PANDEMI COVID-19 - Riyadi, Adhe Bagus; Bulutoding, Lince; Syariati, Namla Elfa (ISAFIR: Islamic Accounting and Finance Review, 2024)
Abstract, This research aims to analyze the comparison of the financial performance of the North Kolaka Regency Regional Government before and after the COVID-19 pandemic. The data used in this research is secondary data obtained from the annual financial reports of the North Kolaka Regency Regional Government for the 2018-2019 and 2021-2022 periods. The data analysis method used is the Paired Sample T-Test hypothesis test to compare the averages of financial variables before and after the COVID-19 pandemic. The research results show that overall there is no significant difference in the financial performance of the North Kolaka Regency Regional Government before and after the COVID-19 pandemic, with a significance value (sig) greater than 0.05. However, there were fluctuations in several financial performance variables between the periods before and after the COVID-19 pandemic. The variables observed include the degree of fiscal decentralization, regional financial dependence, regional financial independence, operating and capital expenditure, efficiency, effectiveness and regional financial growth. Keywords: Degree of fiscal decentralization, regional financial performance, Covid-19 pandemic, regional financial growth, North Kolaka